2013
DOI: 10.1186/1756-0500-6-545
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with burn injury- a cross sectional study from Karachi, Pakistan

Abstract: BackgroundBurn injuries are a major cause of medico legal deaths in Pakistan. The present study was conducted with the aim to assess the mortality rate related to different types of burns injuries.FindingsThis was an observational prospective cross sectional study conducted in Burns Ward of Civil Hospital, Karachi during a period of two years from January 1st 2010 to December 31st, 2011. Data was collected over a questionnaire containing demographic variables as well as date of burn, date of the death (if pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
4
6
1
3
Order By: Relevance
“…Conversely, patients with fire/flame burns or subject to explosions, were at a higher risk of mortality (10.98% and 7.53%, respectively) often tending to include additional injuries, such as inhalation injuries or additional trauma and therefore constitute a significant mortality risk [17]. This concurs with other studies that found that fire was reported to be the most common cause of death [18]. However, there was no significant difference reported between the years 2004-2010 and 1997-2003.…”
Section: Mortality Ratessupporting
confidence: 83%
“…Conversely, patients with fire/flame burns or subject to explosions, were at a higher risk of mortality (10.98% and 7.53%, respectively) often tending to include additional injuries, such as inhalation injuries or additional trauma and therefore constitute a significant mortality risk [17]. This concurs with other studies that found that fire was reported to be the most common cause of death [18]. However, there was no significant difference reported between the years 2004-2010 and 1997-2003.…”
Section: Mortality Ratessupporting
confidence: 83%
“…In Nepal, data acquired from hospital-based studies have been inconsistent in the commonest burn age demographic. While some studies found that the majority of burns occurred in adolescents <15 years old [30][31][32], others demonstrated that age of majority of patients affected and also of those resulting in mortality ranged from 16-40 [33,34] Our results revealed the largest proportion of burns in the age group 25-54 (2.22%), with those aged 0-14 having the second largest proportion (2.08%). Our data highlight that the burns in Nepal has an adult preponderance; unlike other LMICs where burn is regarded as a disease mainly of children.…”
Section: Discussionmentioning
confidence: 46%
“…In a retrospective review of burn patients admitted to Oman's National Burns Unit (NBU) between 1987 and 2011, of 3531 burn patients evaluated, flames and scalds were responsible for 88.4% of burn [32]. Other studies further deconstructed this category, noting that b u r n s 4 1 ( 2 0 1 5 ) 1 1 2 6 -1 1 3 2 flame burns accounted for over two-thirds of burn, with scald comprising one-third or less of the total percent [32][33][34][35][36]. Of approximately 307,000 home injuries reported during 2000-2002 in a national injury surveillance system in Iran, about 125,000 cases (41%) were unintentional burns with 65.2% of domestic injuries occurred in the living rooms or bedrooms followed by 27% in the kitchen, and with scald being the most common type of burn accounting for 77.7% of all burns [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were noted in studies done at Karachi and in central part of India which have reemphasized the correlation. 11,17 More than three fourth of cases were accidental in nature in the present study followed by the suicidal burns. Similar findings were reported from studies conducted across the country.…”
Section: Discussionmentioning
confidence: 92%
“…This is in conformity with the findings of the study conducted in Iran and Karachi. 16,17 There is a decline in the self-repair mechanism of the body tissues as the age increases due to slowing down the metabolic process ultimately leading to complications and mortality.…”
Section: Discussionmentioning
confidence: 99%